2017
DOI: 10.1097/md.0000000000005655
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of refractory obsessive-compulsive disorder

Abstract: Based on both functional and structural studies of excessive activity, fronto-striatal-thalamic-cortical and cortico-striatal circuits have been hypothesized to underlie the pathophysiology of obsessive-compulsive disorder (OCD). However, the neurobiological underpinnings of OCD refractory to medication and therapy remain controversial. This study aimed to evaluate neuroanatomical abnormalities of the whole brain and to evaluate visual processing in patients with refractory OCD.This study was comprised of 2 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The interdiscipline of the neuroimaging and neuropsychology attracts researchers’ attention to the point that ADHD, TS, ODD, and OCD may possess the similar biological mechanism. As mentioned above, five abnormal CSTC circuits are apparently involved in ADHD, including two in ODD (the divided attention and impulsivity/compulsivity circuits; Sebastian et al, 2016) and OCD (the sustained attention/executive function and impulsivity/compulsivity circuits; Jung et al, 2017; Liu et al, 2017), and one in TS (the hyperactivity circuit; Fahim et al, 2010). The damaged range of prefrontal lobe in ADHD spreads wider than in TS, ODD, or OCD, and that quite possibly indicated the dysfunctional area of the CSTC circuits explains the high rate of disease incidence, comorbidity and multiplicity of symptoms in populations.…”
Section: Neuroscience Of Adhdmentioning
confidence: 91%
See 1 more Smart Citation
“…The interdiscipline of the neuroimaging and neuropsychology attracts researchers’ attention to the point that ADHD, TS, ODD, and OCD may possess the similar biological mechanism. As mentioned above, five abnormal CSTC circuits are apparently involved in ADHD, including two in ODD (the divided attention and impulsivity/compulsivity circuits; Sebastian et al, 2016) and OCD (the sustained attention/executive function and impulsivity/compulsivity circuits; Jung et al, 2017; Liu et al, 2017), and one in TS (the hyperactivity circuit; Fahim et al, 2010). The damaged range of prefrontal lobe in ADHD spreads wider than in TS, ODD, or OCD, and that quite possibly indicated the dysfunctional area of the CSTC circuits explains the high rate of disease incidence, comorbidity and multiplicity of symptoms in populations.…”
Section: Neuroscience Of Adhdmentioning
confidence: 91%
“…The specific strength of connectivity between the OFC and ventral caudate/nucleus accumbens decides overall symptom severity (Harrison et al, 2009). In addition, cognitive dysfunction is still linked to the DLPFC circuit abnormality in OCD (Liu et al, 2017). The hypothesis of neural disconnection of CSTC circuit underlies the disorder in both task state and resting state.…”
Section: Neuroscience Of Adhdmentioning
confidence: 99%
“…Supporting that, imaging studies in OCD reveal abnormalities in relevant structures like OFC, limbic system, and DLPFC ( Velikova et al, 2010 ). Also based on Liu et al (2017) study, cognitive dysfunction and compulsive behaviors in patients with OCD are associated with abnormalities within the DLPFC. Their results showed that the resistant OCD subgroup were presented with distractibility and inadequate inhibitory activity.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been hypothesized that punding may be related to plastic changes in the dorsal and ventral striatal structures (7). This model is supported by cortico-striatal disconnections inducing reward-seeking disruption and, in turn, repetitive and stereotypic behavior in both healthy and clinical populations (11,12). In parallel, it was shown that PD patients with punding present with profound deficits in frontal executive functions and severe cortical thinning in the dorsolateral prefrontal and orbitofrontal area, suggesting prefrontal alterations as a critical component in the development of punding (13).…”
Section: Discussionmentioning
confidence: 99%